Investigating reading comprehension challenges among EFL learners in Kumon: A self-directed learning and Tamansiswa perspective - Diahkartika Diahkartika; Dinar Martia Azizah; Hanandyo Dardjito (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2026)
This study aims to describe the reading comprehension challenges faced by EFL students in the Kumon English program, identify their Self-Directed Learning (SDL) practices, and interpret the results using Ki Hadjar Dewantara’s Tamansiswa philosophy as a lens. A qualitative case study was conducted at a Kumon Center in Yogyakarta, Indonesia, with students’ worksheets and semi-structured interviews as the main data sources. The data were analyzed through an interactive qualitative data analysis method. The results indicated that students were able to complete the worksheets at the literal level but faced considerable problems at the inferential and creative levels due to grammatical constraints, limited vocabulary, and lack of self-monitoring. Although the Kumon method emphasizes students’ independence in completing the worksheets, most of the participants still relied on instructor support and rarely engaged in self-review or self-assessment, indicating that independent task completion does not necessarily reflect authentic self-directed learning. The results suggest that from the perspective of Ki Hadjar Dewantara’s Tamansiswa philosophy, it is important to develop learner autonomy incrementally through teacher’s facilitation. The research finds that the combination of Kumon’s systematic learning approach and culturally based educational values can promote learner independence and improve reading comprehension in individualized EFL learning environments.